Peningkatan Keterampilan Guru-guru Sekolah Dasar Melalui Pelatihan Penggunaan Aplikasi Microsoft Office dan Google Education - Lutfi Syafirullah; Riyadi Purwanto; Eka Dyah Puspitasari; Abdul Rohman Supriyono; Devi Taufiq Nurrohman; Arif Fahrizal (Politeknik Negeri Cilacap, 2019)
The teacher is a professional educator who has the duties, functions, and roles to educate the nation's children. In Desa Maos Lor Cilacap, some elementary school teachers experienced problems in using Microsoft Office and Google Docs software as a means used in classroom learning media. In the implementation of community service, this discusses how to improve the knowledge and skills of elementary school teachers in Desa Maos Lor in order to optimize Microsoft Office and Google software in supporting academic and non-academic activities in the school environment. The object of research is elementary school teachers in the Maos region by using the method of delivering material directly to participants accompanied by module guides and independent exercises working on case studies. From the results of the activity, the knowledge of Maos Primary School teachers about the use of Microsoft Office and Google Docs has increased so that all activities are well managed and teachers can complete tasks at school to be more effective and efficient so that the main goal of learning to educate the nation's children can be achieved.